[I226] Quality assurance issues pertaining to nun-uniform dose prescription situations. (August 2018) - Thorwarth, Daniela
Abstract : Abstract: In the last years, non-uniform dose prescriptions have gained a lot of attention as they offer the potential to irradiate tumours adapted to their internal radiation sensitivity which may be locally varying. Such dose painting concepts have been proposed based on functional imaging data, which may be ideal imaging biomarkers to assess individual radiation sensitivities in a locally resolved manner. However, to date this concept has only been applied in a small number of clinical trials which may be due to the high complexity of this approach in terms of imaging, radiation therapy planning and also quality assurance. In this talk, quality assurance of dose painting will be discussed starting from image acquisition and analysis towards implementation of non-uniform dose optimization, dose painting treatment planning and delivery. Furthermore, some clinical examples will be given. Dose painting has been shown to be a very elegant concept for personalized radiation therapy approaches. However, quality assurance of the whole process remains challenging.